The application of Warfarin as FGAR (First Generation Anticoagulant Rodenticide) on the Norway rat (Rattus norvegicus) at Puchong, Selangor - Sharifmalim, Faizulnizam Malim (2018)
Taman Puchong Permai is one of the metropolitan residential parks that is keeping up from time to time in corresponding with the pursuit of advanced state status of Malaysia. Located 25 km from Kuala Lumpur, Taman Puchong Permai also a highly populous area and have a prodigious food destination. The increase in the number of eating outlets in Puchong area has resulted in some unwanted guests, uncontrolled rat’s infestation. These would risk the people being exposed to chronic diseases such as Leptospirosis and Salmonella. In this study, we would like to evaluate the effectiveness of warfarin rodenticide towards Norway rat’s population in the area. Rat population was estimated before and after one-week baiting phase from 2300H until 0000H. Three different areas; dining area (3˚0'40.55''N 101˚35'52.35''E), landfill area (33˚0'39.85''N 101˚35'52.80''E) and residential area (3˚0'39.88''N 101˚35'59.99''E) were selected for this study. The different rat species was found in the area; the Norway rat (Rattus norvegicus) and Asian house shrew (Suncus murinus). The Norway rat population was found to be reduced 35% compared to before warfarin application. The trapping success of the species also affected, where its reduced from 11.11% to 8.70% due to probably trap and bait shyness developed after the baiting. As a nutshell, warfarin is a relevant anticoagulant rodenticide to be used in Taman Puchong Permai to control the population of a commensal rodent; Norway rat. However, proper disposal and food waste management would contribute more to keeping Norway rat population under the threshold.